Impact of nursing robotic assisted surgery education on Kirkpatrick's four levels - Cerruto, Maria Angela; Veronese, Elisabetta; Moretti, Francesca; Mansueti, Nadia; Azzolini, Marianna; Poiesi, Erika; Vezzari, Nicola; Vignola, Erika; Gulotta, Davide; Barp, Andrea; Veccia, Alessandro; Porcaro, Antonio Benito; et al. (Frontiers in Surgery, 2025)
IntroductionAs the robotic surgical burden of diseases increases, the development of skilled surgeons and nursing surgery teams is of fundamental importance. The Kirkpatrick Model is a widely recognised evaluation framework that helps educators assess the impact and effectiveness of educational interventions. However, there is little evidence regarding the effectiveness of robotic surgical training programmes for nursing teams. The study aimed to develop an organisational improvement model to identify the profile of a nurse expert in Robotic Assisted Surgery (RAS) and to define a suitable training programme according to Kirkpatrick's evaluation levels. The model also aimed to increase the number of active robotic rooms while maintaining the same number of staff.MethodsFrom January 2023 to December 2024, a single hospital institution developed an organisational improvement project consisting of the following steps:- Identification of the catalogue of competences of the nurse expert in RAS, using the contributions of personnel already active in this field;- Mapping of competences;- Start of a training programme, evaluated according to the Kirkpatrick model;- Remapping of competences at the end of the training;- Gradual increase in the number of active robotic operating theatres by 2024.ResultsA total of 58 operating room nurses, including the 15 experienced nurses already on staff, had their competencies mapped. At the end of the training programme, 81% of these nurses had achieved the level of competency required to operate a robotic operating room independently, resulting in an overall increase of 154% in the number of active robotic operating rooms per week.DiscussionDetailed planning of training activities dedicated to existing operating theatre nurses, eliminating the need for additional recruitment, together with periodic monitoring of newly acquired skills, has enabled the number of active robotic operating theatres to increase, significantly impacting the company's organisational model.